Ecologia “grigia” e metamorfosi antropologiche. Un contributo - Ubaldo Fadini (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The acceleration of times and modes of existence makes even more urgent the need to outline, albeit partially, a grey ecology (Paul Virilio), capable of dealing with the pollution of distances, of the ‘greatness of nature’, of what is leading to a real ‘twilight of places’, the expression of a progressive impoverishment of our relation with the ‘world’. On this basis – and in relation to the research, among others, of Edgar Morin and Tim Ingold – the question arises again of how precisely to return to live in the latter and of how to concretely think of a ‘new civilization’ (André Gorz) founded on knowing how to live ecologically and politically worthy of the conviction that there is no other wealth in the world itself than living.